The beginning was the end Devo in Ohio - Dellinger, Jade 1967-; Giffels, David 1964- (Series on Ohio history and culture, 2023)
"The beginning was the end is the definitive account of Devo's vibrant early history, from the authors of the first-ever book about the band. The beginning was the end features never-before-seen images of the band members and their visual history as it tells the unlikely story of a collection of creative misfits who formed a musical kinship, drawing material and inspiration from the industrial Midwestern environs of Northeast Ohio. With the May 4, 1970, Kent State shootings as a catalyst, Devo channeled protopunk energy into a sprawling art project that would pioneer the use of music videos, innovate technology in pop music, define the aesthetic of the 1980s New Wave/MTV era, and maintain an edge of social, political, and cultural criticism that continues their relevance fifty years after their formation"--